1998
DOI: 10.1007/s004220050472
|View full text |Cite
|
Sign up to set email alerts
|

Neural network simulations of the primate oculomotor system III. An one-dimensional, one-directional model of the superior colliculus

Abstract: This report evaluates the performance of a biologically motivated neural network model of the primate superior colliculus (SC). Consistent with known anatomy and physiology, its major features include excitatory connections between its output elements, nigral gating mechanisms, and an eye displacement feedback of reticular origin to recalculate the metrics of saccades to memorized targets in retinotopic coordinates. Despite the fact that it makes no use of eye position or eye velocity information, the model ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 86 publications
4
46
0
Order By: Relevance
“…Previous modeling studies have suggested that the effects of SC lesions on saccade metrics can also be reconciled with linear vector summation when intracollicular interactions are incorporated (Badler and Keller 2002;Bozis and Moschovakis 1998;. How SC inputs and intracollicular interactions may shape the SC movement fields, and thereby the SC population activity, is beyond the scope of this study.…”
Section: Effects Of Sc Lesionsmentioning
confidence: 96%
See 1 more Smart Citation
“…Previous modeling studies have suggested that the effects of SC lesions on saccade metrics can also be reconciled with linear vector summation when intracollicular interactions are incorporated (Badler and Keller 2002;Bozis and Moschovakis 1998;. How SC inputs and intracollicular interactions may shape the SC movement fields, and thereby the SC population activity, is beyond the scope of this study.…”
Section: Effects Of Sc Lesionsmentioning
confidence: 96%
“…Note, however, that vector averaging is a nonlinear operation for which it is not obvious how it could be achieved through fixed connections between the SC and the brain stem (Badler and Keller 2002;Bozis and Moschovakis 1998;Groh 2001;. Moreover, the vector-averaging premise for the spatial-to-temporal transformation does not account for the "stretching" of horizontal and vertical saccade components that is needed to obtain straight oblique saccades.…”
Section: Earlier Theories and Controversiesmentioning
confidence: 99%
“…The result is often an "averaging saccade," which lands somewhere in between the spatial locations of the two visual targets (see Chou et al 1999 for a summary of results in this area). Collicular maps with local excitation and longer-range lateral inhibition predict that the two loci of activity generated by the visual stimuli will inhibit each other, but both will excite the locus on the map between the two regions of visual activation (Van Opstal and Van Gisbergen 1989;Arai et al 1994;Das et al 1996;Bozis and Moschovakis 1998). The result will be that these two loci of SC activity will coalesce into a single active site located between the original two.…”
Section: Introductionmentioning
confidence: 92%
“…Previous distributed models of the saccadic system have used lateral inhibitory connections within the superior colliculus (SC) to insure that only a single locus of activity is present on the collicular motor map by the time of saccade onset (Van Opstal and Van Gisbergen 1989;Arai et al 1994;Optican 1994;Massone and Khoshaba 1995;Grossberg et al 1997;Bozis and Moschovakis 1998;Arai et al 1999;Badler and Keller 2002). This type of behavior on a neural map is called winner-take-all.…”
Section: Introductionmentioning
confidence: 99%
“…Models of the SC in saccade generation have been developed primarily using single-point visual stimulation (Lee et al, 1988;Van Opstal and Van Gisbergen, 1989;McIlwain, 1991;Arai et al, 1993aArai et al, ,b, 1994Van Opstal and Kappen, 1993;Das et al, 1996;Bozis and Moschovakis, 1998;Quaia et al, 1998Quaia et al, , 1999. Based on the well known fact that individual saccades are associated with a large population of active SC neurons (Schiller and Koerner, 1971;Wurtz and Goldberg, 1972;Sparks et al, 1976;Sparks and Mays, 1980;Munoz and Wurtz, 1995) and that there are excitatory connections linking large regions of the SC (McIlwain, 1982), the models fall into the general class of distributed coding models (Lee et al, 1988;McIlwain, 1991;Quaia et al, 1998Quaia et al, , 1999.…”
Section: Implications For Population Coding In Scmentioning
confidence: 99%